Comparative Outcomes of Apical Induction Versus Pulp Revascularization in Young Permanent Anterior Teeth with Traumatic Pulp Necrosis - Cheng G; Wu X; Li W; Lv Z (Therapeutics and Clinical Risk Management, 2025)
Gang Cheng, Xiuyin Wu, Wenbo Li, Zhijun Lv Department of Stomatology, People’s Hospital Affiliated to Shandong First Medical University, Jinan, Shandong, People’s Republic of ChinaCorrespondence: Zhijun Lv, Email jkk741@126.comObjective: This study aims to evaluate and analyze the clinical application of pulp revascularization surgery in young permanent anterior teeth with pulp necrosis caused by trauma.Methods: This study selected 40 cases of young permanent anterior teeth with pulp necrosis caused by trauma, treated at our hospital between August 2018 and December 2022. All patients met the complete inclusion criteria and were divided into a study group and a control group based on treatment methods. The study group received pulp revascularization surgery, and the control group received apical induction surgery. There were 20 patients in each group. Comparative observation indicators included clinical treatment outcomes, clinical-related indicators, pain levels, and patient family satisfaction.Results: The treatment outcomes in the study group were significantly better than those in the control group (P < 0.05). The crown-to-root ratio in the study group was lower than that in the control group, and the root canal wall thickness was higher in the study group, with all P < 0.05. The pain level grading in the study group was significantly lower than that in the control group (P < 0.05). Satisfaction indicators for both patients and their families were significantly higher in the study group compared to the control group, with all P < 0.05.Conclusion: Pulp revascularization surgery shows great potential in the clinical application for young permanent anterior teeth with pulp necrosis caused by trauma. It can effectively improve the treatment outcomes, clinical indicators, and alleviate pain, while significantly enhancing patient satisfaction. With continuous research and practice, this advanced treatment method is expected to provide a better oral health experience for patients and promote the development of the dental field.Keywords: pulp revascularization surgery, young permanent teeth, anterior teeth, pulp necrosis caused by trauma, clinical application